A Case of Diversified Dependency: Macrostructural Change and Policy Alternatives in Ecuador. (January 2016) - Gamso, Jonas
After decades of being primarily dependent upon the United States, Ecuador appears to be experiencing a diversification of dependency as alternative sources for trade and investment have emerged to challenge Washington. This diversification is in turn increasing Ecuador's political autonomy, as demonstrated by the Correa administration's policy shift away from the Washington Consensus. Diversified dependency is framing Ecuador's policy options and may frame those of other peripheral states in the context of an increasingly multipolar global economy. Peripheral states will find themselves under pressure from multiple, often competing core states to enact certain policies; at the same time, diversification should provide them leverage in bilateral relations with each of the core states upon which they depend. Después de décadas de depender principalmente de los Estados Unidos, el Ecuador parece estar experimentando una diversificación de su dependencia a medida que surgen fuentes alternativas para el comercio y la inversión que son un desafío a Washington. Esta diversificación a su vez aumenta la autonomía política del Ecuador como lo demuestran los cambios en la política del gobierno de Correa que se sigue apartando del Consenso de Washington. Esta dependencia diversificada está enmarcando las opciones políticas del Ecuador y podría enmarcar las de otros estados periféricos en el contexto de una economía mundial más multipolar. Los estados periféricos recibirán la presión de múltiples estados del centro, con frecuencia rivales, para que aprueben determinadas políticas; a la vez, esta diversificación debería proveerles una ventaja en las relaciones bilaterales con cada uno de los estados del centro de los que dependen.